OPHTHALMIA NEONATORUM in Italy: it is time for change - Cinzia Auriti; Vito Mondì; Salvatore Aversa; Daniele Merazzi; Simona Lozzi; Sergio Petroni; Antonio Baldascino; Luca Massenzi; Roberto Bellù; Stefano Martinelli; Fabio Mosca (BMC, 2021)
Abstract Ophthalmia neonatorum (ON) refers to any conjunctivitis occurring in the first 28 days of life. In the past Neisseria gonorrhoeae was the most common cause of ON. It decreased with the introduction of prophylaxis at birth with the instillation of silver nitrate 2% (the Credè's method of prophylaxis). Today, the term ON is used to define any other bacterial infection, in particular due to Chlamydia Trachomatis. Currently, the WHO reccomends topical ocular prophylaxis for prevention of gonococcal and chlamydial conjunctivitis for all neonates. On the contrary, several European countries no longer require universal prophylaxis, opting for screening and treatment of pregnant women at high risk of infection. And what about Italy? Have a look on Italian history of prophylaxis, starting by the first decree issued in 1940, signed by Benito Mussolini. In the following decades the law has undergone many changes. At the moment, legislation is unclear, therefore careful consideration is required in order to draft the correct appoach.